c - 9; 9 (b, 2004)
Contributed articles on the life and work of Salma Sobhan, social activist and university law teacher from Bangladesh; commemorative volume.
Includes bibliographical references.
AAL
In Bengali; prefatory matter and some articles in English.
Keywords: Sobhan, Salma; Social workers -- Bangladesh -- Biography; Law teachers -- Bangladesh -- Biography; College teachers -- Bangladesh -- Biography